2022
DOI: 10.1002/anie.202113203
|View full text |Cite
|
Sign up to set email alerts
|

A Near‐Infrared Absorbing and Emissive Quadruple Helicene Enabled by the Scholl Reaction of Perylene

Abstract: Herein, we report the synthesis, structural analysis, optical and chiroptical properties of a novel quadruple helicene, which has two [6] and two [7]helicene moieties fused in a contorted framework of 92 sp2 carbon atoms. It was synthesized by the Scholl reaction of a perylene‐containing substrate with the formation of eight carbon‐carbon bonds on the perylene unit in a single synthetic operation. Chemical oxidation of the quadruple helicene with tris(4‐bromophenyl)ammoniumyl hexachloroantimonate resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…This study demonstrates a new example for organic electronic materials based on contorted polycyclic aromatics, which offer interesting electronic and optical properties and self-assembly that are not available to flat π-molecules. This study, together with earlier reports on the cations of multiple helicenes, , leads to a hypothesis that multiple helicenes may be used as a general platform to develop stable π-conjugated radical cations. Further studies to test this hypothesis are in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 58%
“…This study demonstrates a new example for organic electronic materials based on contorted polycyclic aromatics, which offer interesting electronic and optical properties and self-assembly that are not available to flat π-molecules. This study, together with earlier reports on the cations of multiple helicenes, , leads to a hypothesis that multiple helicenes may be used as a general platform to develop stable π-conjugated radical cations. Further studies to test this hypothesis are in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 58%
“…Very recently, Qiu and co-workers reported the Scholl reaction of tetra­(terphenyl)­perylene 201a with rearrangement as shown in Scheme a . Interestingly, Miao and co-workers reported the rearrangement-free Scholl reaction of 201b , which differs from 201a by having methoxy groups attached to the pendant phenyl groups, in the same month and in the same journal . Treatment of 201a with DDQ (12 equiv)/CF 3 SO 3 H gave helical nanographenes 202 and 203 as two regioisomers in a yield of 53% with a ratio of 5:2.…”
Section: Rearrangement In Synthesis Of Curved Polycyclic Aromatics Th...mentioning
confidence: 99%
“…In contrast to double helicenes 29 and 30 , Miao et al 38 reported a quadruple helicene 31 with a perylene core, two [7] helicenes, and [6]helicene units (Figure 8a). Their synthetic strategy was almost the same as that of Qiu et al except for replacing the triphenyl group with a 4-methoxytriphenyl group.…”
Section: Multiple Helicenes With Perylene As the Corementioning
confidence: 99%
“…(d) The UV-vis-NIR and fluorescence spectrum of 31. Adapted with permission 38. Copyright 2022, Wiley.…”
mentioning
confidence: 99%